The Daily Liquidity Effect in a Floor System - Empirical Evidence from the Norwegian Market - Olav Syrstad (Norges Bank, 2012)
This paper analyses the liquidity effect in Norway by examining the relationship between a range of liquidity variables and five different measures of the short-term interbank premium. The models are estimated on data from January 2007 and up to the end of September 2011, a period in which Norges Bank implemented its liquidity policy within a so-called floor system, and prior to the new liquidity system introduced on 3 October 2011. In a floor system the key policy rate is equal to banks' deposit rate in the central bank, and as such, this analysis provides new information on the liquidity effect in a floor system. Both excess liquidity (total central bank reserves in the banking system) and structural liquidity (central bank reserves in the system before Norges Banks' market operations) have, as expected, a negative an significant effect on almost all dependent variables. Structural liquidity is the important factor driving the interbank premiums during periods characterized by low volatility, while excess liquidity gained importance during the financial crisis. This result is in line with what should be expected in a floor system. Furthermore, in periods of financial turmoil European and Norwegian banks may face higher USD rates in the interbank market either because of a general USD liquidity premium or an institution specific credit premium. My analysis provides additional insight in the division between the liquidity premium and the credit premium in a way, to my knowledge, not done in earlier literature. In line with the existing literature, the results indicate that during the financial turmoil and crisis (2007-2009), a USD liquidity premium dominated as credit conditions in USD deteriorated (USD shortage).
hdl:11250/2496825
Keywords: 330